(untitled) (Journal of the College of Basic Education, 2022)
This thesis (Political Instability in Nigeria) based on hypothesis To the effect: ((In spite of the great capabilities that Nigeria possesses - both material and human , it still confronts several challenges - internal and external - that have contributed to the persistence of the phenomenon of political instability In Nigeria, although of the efforts made by the Presidents of the Republic in particular to lift society and the state out of this reality in order to achieve stability and development)). The phenomenon of political instability has accompanied Nigeria from its existence to the present day Nigeria is a linguistically, religiously and ethnically, diverse society, which contributed to exacerbating local conflicts,especially that Nigeria is a country that contains many oil resources, which made it vulnerable to the British occupation which in turn led to the consolidation of the instability of the situation in order to achieve his interests, it did not left until he planted tribal, regional, religious and class differences in conflicts. After Nigeria gained independence from British colonialism and wanted to achieve stability, but it was subjected to The domination of the military establishment through the prevailing coups in the country from time to time under the pretext of removing the bad situation in the country under the slogan of social justice and economic reform, and did not the matter did not stops at this point, but the crises and challenges were raised, until they led to the outbreak of civil war between the eastern province and the federal government to demand independence, and this situation allowed interference some regional and international countries to achieve their interests. After a period of time, especially in (1979), Nigeria achieved a kind of transformation to democracy through a new elected government, but this civilian rule did not achieve what the people aspired to Nigerian, during this period there were economic, social and political challenges, and this matter made Conditions got worse, until the military establishment returned to power, taking advantage of the prevailing circumstances, until return of civilian rule to the country in 1999 through internal and external pressures, which led to establish of a new constitution that outlines the democratic features in the country’s electoral process. And after the democratic transformation that the country witnessed, it wanted to eliminate the phenomenon of lack political stability, but this was not achieved, as it faced a number of challenges, including: Security challenges, represented by the increase in terrorist movements, especially Boko Haram, in light of a crisis Oil, and the government’s failure to take appropriate measures to limit the deteriorating economic conditions contributed In the aggravation of the social and living suffering of the Nigerian society, especially the poor classes, as the percentage increased poverty and the unemployment rate reached serious levels, accompanied by the spread of the phenomenon of administrative financial and political corruption which prevented the success of government plans and programs that were shy and unsuccessful and not feasible, as well as exacerbating debts that, instead of being a solution to social and economic crises, It brought burden society and the state with additional burdens that were paid by the Nigerian people in general,